Electric Drives and Electromechanical Systems - Crowder R. Richard (Oxford, Elsevier, 2006)
Focuses on the selection and application of electrical drives and control systems for electromechanical and mechatronics applications. This title explains the criteria for motor-drive selection, introducing the main types of drives available to drive machine tools and robots. It also provides a review of control systems and their application.